(untitled) (gjstudies, 2026)
This research investigates the underexplored relationship between the qualitativedimensions of accounting regulation enforcement and the formation of corporate compliance incentives, moving beyond traditional economic deterrence models. While priorliterature predominantly focuses on penalty severity and detection probability, thisstudy introduces a novel framework that integrates institutional legitimacy, proceduralfairness, and regulatory signaling as primary drivers of voluntary compliance. We propose that corporations respond not merely to coercive threats but to the perceived legitimacy of regulatory institutions and the fairness of enforcement processes. Througha mixed-methods approach combining archival analysis of enforcement actions from1995 to 2004 and a unique survey of chief financial officers, we examine how variations in enforcement transparency, consistency, and communicative practices influenceinternal compliance investments and ethical climate. Our findings reveal that firmsare significantly more likely to develop robust, proactive compliance programs whenregulators employ transparent, dialogic enforcement strategies that emphasize corrective guidance over punitive sanctions. Conversely, opaque and inconsistently appliedenforcement, even when backed by severe penalties, correlates with minimal, reactivecompliance efforts aimed solely at avoiding detection. The study further identifies a”compliance threshold” effect, whereby beyond a baseline level of deterrence, enhancements in procedural fairness yield greater marginal increases in compliance qualitythan equivalent increases in penalty severity. These results challenge the prevailingenforcement paradigm in accounting regulation and suggest that regulatory agenciescan amplify their effectiveness by strategically cultivating legitimacy and fairness. Thepaper contributes to accounting, regulatory theory, and organizational behavior byproviding a more nuanced, socio-institutional model of compliance motivation, withdirect implications for the design of enforcement regimes and corporate governancepractices.